IFT46 gene promoter-driven ciliopathy disease model in zebrafish - Lee, Mi-Sun; Han, Hye-Jeong; Choi, Tae-Ik; Lee, Kang-Han; Baasankhuu, Amartuvshin; Kim, Hyun-Taek; Kim, Cheol-Hee (Frontiers in Cell and Developmental Biology, 2023)
Ciliopathies are human genetic disorders caused by abnormal formation and dysfunction of cellular cilia. Cilia are microtubule-based organelles that project into the extracellular space and transduce molecular and chemical signals from the extracellular environment or neighboring cells. Intraflagellar transport (IFT) proteins are required for the assembly and maintenance of cilia by transporting proteins along the axoneme which consists of complexes A and B. IFT46, a core IFT-B protein complex, is required for cilium formation and maintenance during vertebrate embryonic development. Here, we introduce transgenic zebrafish lines under the control of ciliated cell-specific IFT46 promoter to recapitulate human ciliopathy-like phenotypes. We generated a Tg(IFT46:GAL4-VP16) line to temporo-spatially control the expression of effectors including fluorescent reporters or nitroreductase based on the GAL4/UAS system, which expresses GAL4-VP16 chimeric transcription factors in most ciliated tissues during embryonic development. To analyze the function of IFT46-expressing ciliated cells during zebrafish development, we generated the Tg(IFT46:GAL4-VP16;UAS;nfsb-mCherry) line, a ciliated cell-specific injury model induced by nitroreductase (NTR)/metrodinazole (MTZ). Conditionally, controlled ablation of ciliated cells in transgenic animals exhibited ciliopathy-like phenotypes including cystic kidneys and pericardial and periorbital edema. Altogether, we established a zebrafish NTR/MTZ-mediated ciliated cell injury model that recapitulates ciliopathy-like phenotypes and may be a vertebrate animal model to further investigate the etiology and therapeutic approaches to human ciliopathies.